2019
DOI: 10.1016/j.cjtee.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine reduces hippocampal microglia inflammatory response induced by surgical injury through inhibiting NLRP3

Abstract: Purpose To investigate whether dexmedetomidine (Dex) can reduce the production of inflammatory factor IL-1β by inhibiting the activation of NLRP3 inflammasome in hippocampal microglia, thereby alleviating the inflammatory response of the central nervous system induced by surgical injury. Methods Exploratory laparotomy was used in experimental models in this study. Totally 48 Sprague Dawley male rats were randomly divided into 4 groups ( n = 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Assembly of the NLRP3 inflammasome triggers cleavage of caspase-1 and induces maturation of the proinflammatory cytokines IL-1β and IL-18, and subsequent cleavage of GSDMD and pyroptotic cell death (Man et al, 2017 ; Shi et al, 2017 ; Voet et al, 2019 ). Our results showed that surgery-induced upregulation of NLRP3 and cleaved caspase-1, and secretion of IL-1β and IL-18, in the hippocampus in aged mice, in agreement with the results of previous studies (Peng et al, 2019 ; Fu et al, 2020 ). Furthermore, surgery-induced upregulation of the GSDMD N domain, the key biomarker of pyroptosis, and the surgery group exhibited more ruptured and TUNEL-positive neurons, a morphological characteristic of pyroptosis.…”
Section: Discussionsupporting
confidence: 94%
“…Assembly of the NLRP3 inflammasome triggers cleavage of caspase-1 and induces maturation of the proinflammatory cytokines IL-1β and IL-18, and subsequent cleavage of GSDMD and pyroptotic cell death (Man et al, 2017 ; Shi et al, 2017 ; Voet et al, 2019 ). Our results showed that surgery-induced upregulation of NLRP3 and cleaved caspase-1, and secretion of IL-1β and IL-18, in the hippocampus in aged mice, in agreement with the results of previous studies (Peng et al, 2019 ; Fu et al, 2020 ). Furthermore, surgery-induced upregulation of the GSDMD N domain, the key biomarker of pyroptosis, and the surgery group exhibited more ruptured and TUNEL-positive neurons, a morphological characteristic of pyroptosis.…”
Section: Discussionsupporting
confidence: 94%
“…(4) The application of dexmedetomidine in some cases of anesthesia in this study could be another compromise. It is believed that dexmedetomidine could reduce the inflammatory response [ 38 40 ] and the incidence of postoperative delirium [ 41 ]. And (5) we did not exclude younger patients (under 65 years old) from this study considering that the inflammation response to the same surgical wound could be the same in young people and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia can be activated by infection, trauma and ischemia, and perform innate immune functions, including the induction of inflammation, cytotoxic effects and modulation of T cell responses via antigen presentation (37). Activated microglia can release inflammatory factors, including TNF-α, IL-1β, IL-6, nitric oxide and prostaglandin E2 (38). These inflammatory factors exhibit a strong toxic effect on neurons and reactivate microglia, aggravating or expanding the inflammatory response of the CNS (39).…”
Section: Discussionmentioning
confidence: 99%